Negative pressure wound therapy with instillation and dwelling (NPWTi-d) for skin graft dressing in hand burns: A case report - Kanako Danno; Ryohei Ishiura; Chihena H. Banda; Yoshimoto Okada; Makoto Shiraishi; Kohei Mitsui; Kento Hosomi; Mitsunaga Narushima (Elsevier, 2024)
Skin graft fixation dressing is important in preventing graft shear and loss which are a major source of morbidity particularly in burn patients. We report the successful use of negative pressure wound therapy with instillation and dwell time (NPWTi-d) in burn injuries of the hand for both skin graft fixation and maintenance of safe hand positioning.A 27-year-old man suffered burn injuries on his hands and face which included deep partial thickness burns of his right hand following an industrial explosion. A day after the injury, early debridement and skin grafting of the hand was performed. NPWTi-d was applied by cutting the form into smaller blocks and stacking them in an overlapping fashion we termed the "Jenga method" to securely fix the skin graft in place and fix the hand in intrinsic plus hand positioning for 1 week. The device was set to 10 ml saline immersion for 3 min every 3.5 h and section pressure reduced from −125 mmHg to −75 mmHg due to hand discomfort. Graft take was 95 % and the patient recovered with no joint contracture or other complications.We report this case to demonstrate the use of NPWTi-d for effective skin graft fixation and non-invasive immobilization of the hands and fingers in a safe limb position in a patient with burn injuries and present the stacked block foams "Jenga method" as a useful easy technique for application of NPWT.